(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
The physical training system of cadets in military and law enforcement educational institutions must ensure a high level of physical fitness, functional readiness, and adaptive capacity. Traditional training methods, while effective, often lack variability and motivation. Football-based training has gained attention as a multifunctional physical activity; however, scientifically substantiated training load parameters adapted to cadets remain insufficiently studied.